2013
DOI: 10.1038/cdd.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

USP7 and Daxx regulate mitosis progression and taxane sensitivity by affecting stability of Aurora-A kinase

Abstract: A large number of patients are resistant to taxane-based chemotherapy. Functional mitotic checkpoints are essential for taxane sensitivity. Thus, mitotic regulators are potential markers for therapy response and could be targeted for anticancer therapy. In this study, we identified a novel function of ubiquitin (Ub)-specific processing protease-7 (USP7) that interacts and cooperates with protein death domain-associated protein (Daxx) in the regulation of mitosis and taxane resistance. Depletion of USP7 impairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 60 publications
5
66
0
Order By: Relevance
“…Recently, RNA interference (RNAi) was used to systematically screen cancer‐related USPs in the human genome . In this model, USP7 silencing exerted selective antiproliferative effects by inducing cell‐cycle arrest, although only in cancer cells retaining wild‐type (WT) p53 . Consistent with these reports, USP7 silencing increases steady‐state p53 levels by promoting murine double minute 2 homolog (Mdm2) degradation .…”
supporting
confidence: 78%
“…Recently, RNA interference (RNAi) was used to systematically screen cancer‐related USPs in the human genome . In this model, USP7 silencing exerted selective antiproliferative effects by inducing cell‐cycle arrest, although only in cancer cells retaining wild‐type (WT) p53 . Consistent with these reports, USP7 silencing increases steady‐state p53 levels by promoting murine double minute 2 homolog (Mdm2) degradation .…”
supporting
confidence: 78%
“…In our experiments we observed that mitotic timing was considerably longer by cyclin B stability or time lapse microscopy in USP7 depleted cells ([46], Fig. 5C and D) and in cells exposed to USP7 inhibitors (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…CellMiner previously has enabled us to: i) identify promoter-proximal transcriptional pausing in human genes (37, 38), ii) discover the helicase SLFN11 as a causal determinant of response to DNA-damaging agents (18), iii) recognize the regulation of MYC expression by miR-375 (39), iv) recognize the importance of MYC as a driver of mitochondrial genes (40), v) reveal genetic inactivation or endogenous activation of CHEK2 across the NCI-60 (40); vi) link USP7 and Daxx to taxane resistance (41), vi) link TP53 wild type status, Mdm2 transcript level, and miR-34a transcript level with nutlin activity (10), viii) reveal the interrelationship between RAS (H, K, and NRAS)-BRAF-PTEN mutational status, EGFR expression, and ERBB2 expression with erlotinib activity (10), ix) demonstrate the strong correlation between ABCB1 expression and doxorubicin activity (2), x) recognize both known and novel genes expression levels, microRNA expression levels, and drug activities with a colon-specific pattern input to “Pattern comparison” (2), xi) identify predominant co-regulation among cell migration genes (42), xii) identify co-regulation among kinetochore genes, their prospective regulatory elements, and their association with genomic instability (43), xiii) show the connection between accumulation of mass homozygotes in the cancer cell lines as compared to non-cancerous HapMap trios (44), xiv) identify the drug Ro5-3335 as a candidate treatment for core binding factor leukemias (45), xv) associate CDKN2A DNA copy number and expression to mitoxantrone activity (8), xvi) define an epithelial gene expression signature (46), and xvii) recognize the composite relationship between the mutational status of multiple genes from the EGFR-ERBB2 pathway and drug response, including the directionality of that influence as a function of molecular pathway considerations (14). The diversity among these observations gives an indication of the boundless scope and range of the types of possible discoveries that can be made using the NCI-60 database and CellMiner set of tools.…”
Section: Discussionmentioning
confidence: 99%